Size-dependent piezoelectric and mechanical properties of electrospun P(VDF-TrFE) nanofibers for enhanced energy harvesting. Issue 6 (25th January 2016) - Ico, Gerardo; Showalter, Adam; Bosze, Wayne; Gott, Shannon C.; Kim, Bum Sung; Rao, Masaru P.; Myung, Nosang V.; Nam, Jin
Abstract : Dimensional reduction of electrospun P(VDF-TrFE) increases crystallinity (DOC), electroactive phase content (EA), Young's modulus ( E ) and piezoelectric coefficient ( d 33 ), collectively leading to enhanced piezoelectric energy harvesting efficiency. Abstract : Piezoelectricity-based energy harvesting from wasted mechanical energies has garnered an increasing attention as a clean energy source. Especially, flexible organic piezoelectric materials provide an opportunity to exploit their uses in mechanically challenging areas where brittle inorganic counterparts have mechanical limitations. In this regard, electrospinning has shown its advantages of producing poly(vinylidene fluoride) (PVDF)-based nanofibrous structures without the necessity of a secondary processing to induce/increase piezoelectric properties. However, the effects of electrospun fiber dimension, one of the main morphological parameters in electrospun fibers, on piezoelectricity have not been fully understood. In this study, two dependent design of experiments (DOEs) were utilized to systematically control the dimensions of electrospun poly(vinylidene fluoride-trifluoroethylene) (P(VDF-TrFE)) to produce nanofibers having their diameter ranging from 1000 to sub-100 nm. Such a dimensional reduction resulted in the increase of piezoelectric responsible electroactive phase content and the degree of crystallinity. These changes in crystal structure led to approximately 2-fold increase in piezoelectric constant as compared to typical P(VDF-TrFE) thin films. More substantially, the dimensional reduction also increased the Young's modulus of the nanofibers up to approximately 80-fold. The increases in piezoelectric constant and Young's modulus collectively enhanced piezoelectric performance, resulting in the exponential increase in electric output of nanofiber mats when the fiber diameters were reduced from 860 nm down to 90 nm. Taken together, the results suggest a new strategy to improve the piezoelectric performance of electrospun P(VDF-TrFE) via optimization of their electromechanical and mechanical properties.